The Influence of the Gut Microbiome on the Pathogenesis of Asthma: A Review of Current Research and Therapeutic Options - Feret, Dominik Maciej; Zapasek, Daniel; Szczepański, Michał; Kuliga, Marcin; Bajak, Mateusz; Słowik, Julia; Inglot, Julia; Inglot, Jadwiga; Mamczur, Maciej; Sowa, Damian (Quality in Sport, 2024)
Introduction and purpose: Asthma is a chronic inflammatory disease of the airways. Its pathogenesis may be linked to the gut microbiome, which plays a key role in the immune system. This review analyzes current evidence regarding the influence of the gut microbiome on asthma development, particularly in the context of the gut-lung axis. The aim of this paper is to assess the current therapeutic possibilities for asthma based on the modulation of the gut microbiota. Materials and methods: The literature review includes articles from scientific databases (PubMed), selected for their citation impact and relevance to the topic under analysis. Results: The gut microbiota affects immune balance by producing short-chain fatty acids (SCFAs) and other metabolites that modulate the body’s inflammatory response. Gut dysbiosis may contribute to the development of asthma. The use of probiotics, prebiotics, and a fiber-rich diet has shown beneficial effects in reducing inflammation in asthma. Fecal microbiota transplantation (FMT) may represent a future therapeutic approach, though further clinical research is required. Conclusion: Modulation of the gut microbiota is a promising support in asthma therapy. A personalized treatment approach based on the patient’s microbiota profile could potentially improve disease control and reduce the reliance on steroids in the future.